Original papersUsefulness of dermoscopy for diagnosing pearly penile papules - Michajłowski, Igor; Włodarkiewicz, Adam; Florczak, Konrad; Michajłowski, Jerzy; Sobjanek, Michał; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: Introduction: In the differential diagnosis of pearly penile papules there should be considered: ectopic sebaceous glands, genital warts, molluscum contagiosum and rarely lichen nitidus. In connection with the wide spread of human papilloma virus, pearly penile papules are often misdiagnosed as genital warts. Aims: To research specific, typical features of pearly penile papules in dermoscopy and determine the usefulness of this method in differential diagnosis of pearly penile papules and genital warts. Material and methods: Seven patients with isolated PPP and 5 patients with coexisting PPP and genital warts were subjected to clinical and dermoscopic examination. Results: Pearly penile papules in dermoscopy were observed as pink and whitish cobblestones situated in one or several rows. Each papule contained central dotted or comma-like vessels and was surrounded by crescent-shaped structures. The dermatoscopic picture of genital warts was dominated by an irregular vascular system containing many punctate (dotted) vessels or more bigger vessels (red globules). Also, a pathognomonic feature was the presence of red or black dots corresponding with intravascular clots. Conclusions: Finding the above-mentioned dermatoscopic features of pearly penile papules allows one to establish the diagnosis and to restrict the use of therapy. Also, differentiation of pearly penile papules and genital warts in patients with both diseases coexisting allows one to restrict the area of treatment.